2012
DOI: 10.1136/annrheumdis-2012-201730
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in the human posterior cruciate ligament during aging and osteoarthritis: correlations with anterior cruciate ligament and cartilage changes

Abstract: Objectives-To determine the histological patterns of posterior cruciate ligament (PCL) degeneration during aging and in relation to changes in articular cartilage and anterior cruciate ligament (ACL) across the entire adult age spectrum.Methods-Human knee joints (n=120 from 65 donors) were processed within 72 hours postmortem. Articular cartilage surfaces were graded macroscopically. Each PCL was histologically evaluated for inflammation, mucinous changes, chondroid metaplasia, cystic changes and orientation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 40 publications
4
45
0
1
Order By: Relevance
“…The pathological chondrogenesis of ligaments described in mouse knee joints in this study also shows many similarities to human joints [44,45]. It has been found that human cruciate ligaments from OA patients show important chondroid and cartilage metaplasia, which involve a change in ligament cell phenotype to a more chondrocyte-like round cell morphologies [34,46]. This included positive Col2…”
Section: Discussionsupporting
confidence: 67%
“…The pathological chondrogenesis of ligaments described in mouse knee joints in this study also shows many similarities to human joints [44,45]. It has been found that human cruciate ligaments from OA patients show important chondroid and cartilage metaplasia, which involve a change in ligament cell phenotype to a more chondrocyte-like round cell morphologies [34,46]. This included positive Col2…”
Section: Discussionsupporting
confidence: 67%
“…Although there were subtle differences in meniscus pathology across loading groups and time points, our findings of meniscus and PCL pathology in the mouse were consistent with the observations that they are associated with cartilage damage and OA in humans343536. Additionally, our findings of gradual increase in osteophyte count over time (especially in 12N group) in loaded knees is consistent with another study of ACL transection in mice37.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to aging studies in the human meniscus, the anterior [10••] and posterior[11] cruciate ligaments (ACL and PCL respectively) have also been studied. Similar to the meniscus work noted above by Pauli et al[7••], the same group used human donor tissue and compared changes in the ACL and PCL to those in cartilage from the same joints.…”
Section: Aging Changes In Tissues Other Than Cartilage Which May Contmentioning
confidence: 99%